Conduction mechanisms in Ti/HfOx/Pt resistive switching memory device - Tan, Kuan Hong (Nanyang Technological University, 2020)
Conduction mechanisms of Ti/HfOx/Pt Resistive Random Access Memory (RRAM) were investigated in this work. I-V characteristics of RRAM devices were measured and Ohmic conduction was found to be the dominant conduction mechanism in low resistance state (LRS), while Schottky emission (SE) was found to dominate in high resistance state (HRS). In addition, multi-level states of Ti/HfOx/Pt devices in HRS were investigated, which device resistances in HRS differ under various RESET voltages. Different RESET voltages also vary the conduction mechanisms, which at -0.9V RESET was found to be SE while that of -1.0V, -1.1V and -1.2V were hopping conductions. From fitted graph of hopping conduction, the distance between traps within HfOx was found to be ~0.8 nm and the traps energy level below bottom of conduction band is ~0.85 eV. -1.3V RESET voltage resulted in Poole-Frenkel emission is the main conduction mechanism. The traps for Poole-Frenkel emission are found ~0.5 eV below the conduction band. In the end of the report, the electric field within hafnium oxide was simulated. The electric field was found to be stronger at the region near the edges of electrodes. In this case, conducting filaments will most likely to form in that region. Furthermore, oxygen vacancies will tend to accumulate at the tip of conducting filaments, due to the greater electric field near that region. This phenomenon results in the growth of conducting filaments.